IMPLEMENTATION OF PAI LEARNING STRATEGY INNOVATIONS (STUDIES at SMA AL AZHAR MEDAN) - Salim, Salim (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to find out innovations in PAI learning at SMA Al Azhar Medan. This study uses a qualitative approach. Data collection was carried out using interview techniques, observation, and documentation studies. The aim is to reveal the problem of innovation in PAI learning strategies. The key informants in this study were school principals and PAI teachers with predetermined criteria. The results of the research findings based on the data collection techniques used are as follows: The learning strategy applied at SMA Al Azhar Medan has experienced innovations, namely by implementing active learning in the classroom by involving students to carry out investigations with real situations found directly by students in the environment they face. Learning activities are trained in how students compile their knowledge according to the experience and knowledge they have.